RepositóriUM: implementing DSpace in portuguese: lessons for the future and research pathways - Rodrigues, Eloy (2004)
In this paper we describe the implementation of the Minho University (UMinho) Institutional Repository (RepositóriUM), Portugal. UMinho translated and has been using the first Portuguese version of DSpace, an Open Source software system developed in a partnership of the Massachusetts Institute of Technology (MIT) and Hewlett-Packard (HP). The five phases established for the implementation plan are pointed out in this work (1. installation, translation, and configuration; 2. upload of thesis and dissertations; 3. establishment of pilot communities; 4. making the repository public, and 5. opening to the overall UMinho community), as well as, the reasons that led to the choice of the six pilot communities of different areas of knowledge (Information Systems; Polymers Engineering; Biological Engineering; Management, and one from the Humanities and another from the Social Sciences areas) to participate in this implementation period. In this paper we wish to share the lessons learnt, and the pathways for research, in particular for cross-cultural research, according to some questions and observations obtained during the first 10 months of experience. With this information as a background, some research pathways have been identified and are starting to be further developed in the context of MSc or PhD research at UMinho.